Development and investigation of novel transition metal mediated reactions in porphyrin chemistry - Horn, Sabine (Trinity College (Dublin, Ireland). School of Chemistry, 2009)
The aim of this work was to extend the number of existing pathways for the synthesis of porphyrins. The focus was directed towards the development and investigation of new transition metal catalysed reactions in porphyrin chemistry. These methods could then be used for the synthesis of distinct porphyrin systems for various applications. A new pathway was discovered and investigated for the synthesis of acroleinylporphyrins. These compounds serve as precursors for the synthesis of benzochlorins which are highly promising candidates for photodynamic therapy. The new synthetic method included the conversion of allylporphyrins into nickel(II) acroleinylporphyrins in good yields via a nickel(II) mediated reaction. It demonstrates the first example of a nickel catalysed reaction in porphyrin chemistry. This methodology could be applied to aryl- and alkyl-substituted porphyrins with different substitution patterns. However, it was found to be limited to the meso-position of either free-base or nickel(Il) metallated porphyrins. Nevertheless, the developed method offered a good alternative to the existing pathways for the synthesis of acroleinylporphyrins.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin